THE CREATION OF THE ARMADILLO CAREER READINESS SKILLS GAP PROGRAM AT RANDOLPH COMMUNITY COLLEGE: CLOSING THE CAREER GAP FOR HIGH SCHOOL JUNIORS - Cheeks, Ivry S. (East Carolina University, 2018)
The task of making important career decisions for many individuals and especially high school students occur during high school and beyond. Preparing students to be ready for work, life, and citizenship will require a different approach that would still focus on career and college readiness. New outcomes for what students need to know and be able to do, would require a different orientation for teaching and learning in the classroom. Having a way to bridge the gap between high school students and educational opportunities leading to employment is a problem facing leaders in Randolph County and Randolph Community College. There is not a program in place to address the career readiness skills gap when working with the high school students in the Career and College Promise Program at Randolph Community College. According to the Randolph County Environmental Data Scan published in November of 2015, 44.7% of the county's labor force is over the age of 44. The county needs a skilled labor force to support the local businesses and industries as the preretirement workers continue to age. Additionally, those members of the population who are 25 years and older living to poverty are only 27.5% for college attendees and graduates as compared to 72.5% for those with a high school diploma or less. The goal of the Armadillo Career Readiness Skills Gap Program is one approach to addressing local workforce development needs and closing the career readiness gaps while connecting education to a career goal for students.
Keywords: Career Readiness; Workforce; Career and College Promise Initiative; Community college student development programs--North Carolina--Asheboro; High school students--Vocational guidance--North Carolina--Asheboro; Randolph Community College